ROLE OF QUALITY EDUCATION FOR SUSTAINABLE DEVELOPMENT GOALS (SDGS) - Nazar, Raima; Chaudhry, Imran Sharif; Ali, Sajid; Faheem, Muhammad (PEOPLE: International Journal of Social Sciences, 2018)
At this critical time, the best thing that the government can do to stimulate progress is to provide the nation with the best minds to help the nation tackle future challenges. Now that the race towards the attainment of the Sustainable Development Goals (SDGs) is on, it is pertinent to set the key performance indicators for assessing progress in line with the overall vision of the development agenda. In this paper, the role of quality education for sustainable development goals (SDGs) is explored. Quality education is called SDG-4 because it is a 4th goal of the SDGs. The introduction and background of the quality education and sustainable development goals is defined in first section. In section 2, some relevant theories about the role of education in development are presented. Literature review of some selected studies is given in section 3 of the study. In section 4 of the study, the comparison is made among SDG-4, MDG-2 (Goal-2 of Millennium Development Goals) and EFA (Education for All) and reasons are given that how SDG-4 is differ from MDG-2 and EFA. In next section, it is defined that how we can achieve equitable and good quality of education and some priority targets will be set to achieve the goal. The challenges for higher education and the steps involved in translating global commitments are given in subsequent section. At the end, the conclusion of the study is given.